A efetividade da lei 9.605/98 em crimes contra a flora praticados por pessoas jurídicas em Sergipe - Filipin, Ana Lúcia Oliveira (2015)
The State of Sergipe currently has a significant deficit in its vegetation and that situation can be attributed to lack of a state policy that prioritizes forests, for example, forest restoration and planting of exotic species to fill the energy demand. Contributes to this framework, the aggressions against Flora caused by legal entities, considered by existing legislation as environmental crimes. In this sense, this research has as main objective to evaluate the effectiveness of the law 9.605 / 98, by identifying, in tax assessments, crimes against Flora by a legal entity, applied by IBAMA in the State of Sergipe in the period 2000 to 2011. the specific objectives aimed to identify the number of cases that were resolved at the administrative level and its consequences, and to identify the type of legal treatment of the processes of environmental crimes against Flora. This research is classified as documentary, exploratory, descriptive and qualitative-quantitative. To achieve the required purpose, 17 cases were analyzed in IBAMA headquarters in the period June-August 2014, which were selected crimes of destruction, deforestation and fire Flora, to evaluate the effectiveness of the Law of environmental crimes at the administrative , civil and criminal, with special emphasis on process duration and the payment of administrative fine. In possession of the existing geographical coordinates processes, it was possible to generate a map of the environmental degradation caused by Legal Entities in the state of Sergipe, leading to the conclusion that the Law 9.605 / 98 does not achieve the aims for which it was developed. Since it was found that at the administrative level there was a low percentage of fines collected and recovered areas, that in criminal cases the defendants were acquitted or sentenced to moved around penalties and crimes considered less offensive potential and in the civil sphere no concrete action was implemented.